Hydrazine Synthase From Anammox Is Inhibited by Linear and Aromatic Alkynes - Cerys Maryan; Guylaine H. L. Nuijten; Andrew T. Crombie; Sebastian Lücker; Victoria Gibson; Marcela Hernández; J. Colin Murrell; Laura E. Lehtovirta‐Morley (Environmental Microbiology, 2026)
N 2 O emissions by nitrifiers are often estimated using selective inhibitors, such as 1‐alkynes. However, the effects of these inhibitors on anaerobic ammonium‐oxidising (anammox) bacteria are largely unknown. In this study, we assessed the inhibitory effect of linear and aromatic alkynes on anammox activity and identified their target enzyme. ‘ Candidatus Kuenenia stuttgartiensis’ biomass and constructed wetland soil samples were incubated with 10 μM of C 2 –C₈ linear alkynes or phenylacetylene for 10 days. Anammox activity was determined using the isotopic tracer 15 N‐nitrite and 29 N 2 production. Anammox activity was suppressed by C 2 –C 5 alkynes, whereas the larger or aromatic alkynes caused no inhibition. However, hydrazine oxidation activity was not affected, indicating that C 2 –C 5 alkynes inactivated enzymes upstream of hydrazine dehydrogenase. In incubations using an NO donor and 15 N‐ammonium, 29 N 2 production stopped, suggesting that hydrazine synthase was the target of these alkynes. A comparable trend was observed in the wetland samples, but with a less pronounced reduction in 29 N 2 production. Since alkynes >C 5 did not affect anammox, these findings demonstrate the suitability of using 1‐octyne as a selective inhibitor to quantify N 2 O contributions from ammonia‐oxidising bacteria (AOB) versus ammonia‐oxidising archaea (AOA) in oxic/anoxic interface environments.